Making every birth count: Outcomes of a perinatal mortality audit program. (1st April 2021) - Flenady, Vicki; Kettle, Imogen; Laporte, Johanna; Birthisel, Deborah; Hardiman, Leah; Matsika, Admire; Whelan, Nikki; Lehner, Christoph; Payton, Diane; Utz, Miles; Wojcieszek, Aleena M.; Lawford, Harriet; et al.
Abstract : Background: Stillbirth rates have shown little improvement for two decades in Australia. Perinatal mortality audit is key to prevention, but the literature suggests that implementation is suboptimal. Aim: To determine the proportion of perinatal deaths which are associated with contributing factors relating to care in Queensland, Australia. Materials and Methods: Retrospective audit of perinatal deaths ≥ 34 weeks gestation by the Health Department in Queensland was undertaken. Cases and demographic information were obtained from the Queensland Perinatal Data Collection. A multidisciplinary panel used the Perinatal Society of Australia and New Zealand (PSANZ) perinatal mortality audit guidelines to classify the cause of death and to identify contributing factors. Contributing factors were classified as 'insignificant', 'possible', or 'significant'. Results: From 1 January to 31 December 2018, 65 deaths (56 stillbirths and nine neonatal deaths) were eligible and audited. Most deaths were classified as unexplained (51.8% of stillbirths). Contributing factors were identified in 46 (71%) deaths: six insignificant (all stillbirths), 20 possibly related to outcome (17 stillbirths), and 20 significantly (16 stillbirths). Areas for practice improvements mainly related to the care for women with risk factors for stillbirth, especially antenatal care. The PSANZ guidelines were applied and enabled a systematic approach. Conclusions: A high proportion of late gestation perinatal deaths are associated with contributing factors relating to care. Improving antenatal care for women with risk factors for stillbirth is a priority. Perinatal mortality audit is a valuable step in stillbirth prevention and the PSANZ guidelines allow a systematic approach to aid implementation and reporting.